Upper Extremity Nerve Compression Syndromes – More Than Just a Carpal Tunnel Syndrome: A Review Article - Kasapinova, Katerina; Kamiloski, Viktor; Atanasovska, Emilija; Spasovska, Katerina (Scientific Foundation SPIROSKI, Skopje, Republic of North Macedonia, 2025)
BACKGROUND: Besides carpal tunnel syndrome and cubital tunnel syndrome, other nerve entrapment sites in the upper extremity are less recognized. Only half of the upper extremity compression neuropathy syndromes are actually carpal tunnel and cubital tunnel compressions. This suggests that the rest of the entrapment syndromes are potentially not treated adequately. They are often misdiagnosed or the level of compression is not being distinguished. AIM: To raise awareness of compression syndromes (other than the carpal tunnel) in the arms and to describe the clinical triad to diagnose them. METHODS: This is a narrative review of the clinical features of the compression syndromes of the median, ulnar, and radial nerves in the upper extremities. The diagnostic triad for each syndrome is analyzed. The review focuses especially on the lacertus syndrome and describes the surgical release. CONCLUSION: A correct diagnosis is essential for targeted treatment of upper extremity nerve compression syndromes. It should also include an assessment of individual muscle strength, which is a critical part of the clinical neurological tests.
Keywords: Nerve compression syndrome; Nerve entrapment; Upper extremity; Manual muscle strength testing; Lacertus syndrome